Determinación de las propiedades mecánicas de eco bloques a partir de botellas recicladas PET combinado con neumáticos usados. Maynas – 2025 - Arévalo Pizango, Sara Elian (2025)
In Maynas–Loreto (Peru), the build-up of PET bottles and end-of-life tires calls for circular solutions suitable for non-structural construction. This study assessed eco-blocks made from recycled PET and crumb rubber at three PET/rubber ratios (90/10, 95/5, 98/2) using a quantitative experimental design (n = 5 per mix) to measure density, water absorption, and compressive strength; assumptions were checked with Shapiro–Wilk and Levene, and means were compared via one-way ANOVA or Welch with Tukey/Games–Howell as appropriate. Mean values were: density 1354, 1335, 1329 g/cm³; water absorption 4.57, 6.64, 8.60 %; compressive strength 4.08, 3.36, 4.40 MPa for 90/10, 95/5, and 98/2, respectively. Homogeneity held for density (p = 0.774) and absorption (p = 0.285) but not for strength (p = 0.036), thus strength was tested with Welch (F (2,7.076) = 1.457, p = 0.295). Significant differences arose in density (F (2,12) = 6.003, p = 0.016; Tukey: 90/10 > 98/2, p = 0.015) and absorption (F(2,12) = 5.613, p = 0.019; Tukey: 90/10 < 98/2, p = 0.015). Overall, all mixes suit non-structural use; the 5–10 % rubber range delivered the best trade-off between low absorption and process consistency, with 90/10 excelling in lower absorption and higher density. Field pilots and durability testing (UV, wet–dry cycling) are recommended for deployment in lightweight partitions, enclosures, and raised walkways in flood prone areas of Maynas.